Evaluation of Acute and Chronic Anti-inflammatory Effects and Anti-nociceptive Effect of Novel Preparation Sudarshana Suspension - Weerakoon, W.A.S.S.; Perera, P.K.; Gunasekera, D.; Suresh, T.S. (European Modern Studies Journal, 2024)
Sudarshana Suspension (SS) is a novel Ayurveda preparation. The main aim of this study was to evaluate the acute and chronic anti-inflammatory and antinociceptive potential of Sudarshana suspension in Wistar rats. The acute anti-inflammatory potential of the Sudarshana suspension was evaluated using the carrageenan-induced paw oedema method and the chronic anti-inflammatory activity of SS was tested using the adjuvantinduced arthritis rats’ model. Anti-nociceptive activity was tested using the model of acetic acid-induced writhing in rats. SS significantly inhibited carrageenan-induced paw oedema, comparable with the known anti-inflammatory drug, Indomethacin. The maximum inhibitions of test drugs, SS were 88.5%, at the 5th hour following drug administration, whereas indomethacin produced 96.2 % inhibition at the same hour. Induction of arthritis significantly increased footpad thickness (FPT), hind paw ankle joint thickness (AJT), and loss of Body Weight (BW). Treatment with SS and standard drug Celecoxib in the arthritic animals produced significant reductions (p < 0.001) in AJT, and FPT, reducing erythema and oedema in the ankle joints and footpad of the adjuvant-induced arthritis rats and normalized BW. When compared to the negative control by acetic acid-induced writhing in rats, the SS showed statistically significant (p< 0.05) inhibition of writhing (34.15%) while the standard drug diclofenac showed 40.98% inhibition of writhing in experimental animals. Sudarshana Suspension possesses statistically significant acute and chronic anti-inflammatory effects comparable to Indomethacin and Celecoxib. Moreover, it possesses statistically significant anti-nociceptive effects that are closely similar to diclofenac sodium.
Keywords: Acute and Chronic Anti-inflammatory effect; anti-nociceptive effect; Wistar Rats; Sudarshana Suspension